Conduction Mechanisms in BaTiO3–Bi(Zn1/2Ti1/2)O3 Ceramics. Issue 9 (30th May 2016) - Kumar, Nitish; Patterson, Eric A.; Frömling, Till; Cann, David P.
Abstract : Polycrystalline BaTiO3 –Bi(Zn1/2 Ti1/2 )O3 (BT–BZT) ceramics have superior dielectric properties for high‐temperature and high‐energy density applications as compared to the existing materials. While it has been shown that the addition of BZT to BT leads to an improvement in resistivity by two orders of magnitude, in this study impedance spectroscopy is used to demonstrate a novel change in conduction mechanism. While nominally undoped BT exhibits extrinsic‐like p ‐type conduction, it is reported that BT–BZT ceramics exhibit intrinsic n ‐type conduction using atmosphere‐dependent conductivity measurements. Annealing studies and Seebeck measurements were performed and confirmed this result. For BT, resistivity values were higher for samples annealed in nitrogen as compared to oxygen, whereas the opposite responses were observed for BZT‐containing solid solutions. This suggests a fundamental change in the defect equilibrium conditions upon the addition of BZT to the solid solution that lowered the carrier concentration and changed the sign of the majority charge carrier. This is then also linked to the observed improvement in resistivity in BT–BZT ceramics as compared to undoped BT.